2018
DOI: 10.1007/s11046-018-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pulmonary Aspergillosis Complicated by Carbapenem-Resistant Pseudomonas aeruginosa Infection During Pembrolizumab Immunotherapy for Metastatic Lung Adenocarcinoma: Case Report and Review of the Literature

Abstract: The widespread use of T lymphocyte-associated antigen-4 (CTLA-4) and programmed death (PD)-1 and PD ligand-1 (PDL1)-targeted agents in cancer patients as immunotherapy has raised some issues on their safety profile. Regarding infectious complications, it has emerged that these compounds do not intrinsically increase susceptibility to opportunistic infections, which mainly correlate with the co-administration of systemic immunosuppressive therapy (high-dose corticosteroids and anti-tumor necrosis factors inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Since different lymphocyte phenotypes are also correlated with different lymphocyte function, we first established an immune scoring model based on combination of the number, function and phenotype of lymphocytes to comprehensively assess host immunity. The imbalance of immunity leads to many immune-related diseases, such as autoimmune disease (hyperimmune status) [30] and opportunistic infection (hypoimmune status) [31][32][33][34][35][36]. The validation data from patients with different immune status showed that the model had high sensitivities in the determination of both hyperimmune and hypoimmune status.…”
Section: Discussionmentioning
confidence: 99%
“…Since different lymphocyte phenotypes are also correlated with different lymphocyte function, we first established an immune scoring model based on combination of the number, function and phenotype of lymphocytes to comprehensively assess host immunity. The imbalance of immunity leads to many immune-related diseases, such as autoimmune disease (hyperimmune status) [30] and opportunistic infection (hypoimmune status) [31][32][33][34][35][36]. The validation data from patients with different immune status showed that the model had high sensitivities in the determination of both hyperimmune and hypoimmune status.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of IA have also been reported in pediatric patients with solid tumor with a very low incidence or prevalence. 73,74 Rare cases of IA have been reported in patients with solid tumor treated with targeted anticancer therapies: gefitinib (epidermal growth factor receptor tyrosine kinase inhibitor), 75 bevacizumab (antivascular endothelial growth factor monoclonal antibody), 76,77 pembrolizumab and nivolumab (anti-PD-1 receptor monoclonal antibody), 78,79 temsirolimus (inhibitor of m-TOR). 80 An acute progression of a chronic pulmonary aspergillosis has been observed in a patient receiving nivolumab.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…As shown in Table 2, pembrolizumab-induced pneumonitis developed with variable intervals after treatment, ranging from 1 week to 2 years. [918] Pneumonitis occurred after diverse dose (median, 4 doses) of PD1 inhibitor treatment, ranging from 1 to 38 doses. [8] Regarding the risk factors for pembrolizumab-induced pneumonitis, little is known, but smoking, prior treatment, lung cancer, prior thoracic radiotherapy, and prior lung disease were suggested to promote pneumonitis development.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous case reports, almost all cases were treated with steroid and more than 60% received antibiotics (Table 2). [918] However, descriptions of the accompanying infections were lacking (Table 2). According to the multicenter study, 60% (3 of 5) of the fatal cases had accompanying infections.…”
Section: Discussionmentioning
confidence: 99%